Regalo de navidad - Fischer, Konrad (1995)
The case presents a qualitative situation that has been developed following the methodology of the classics of economics, i.e., philosophical, from which logic, which laid the foundations of the knowledge of economics, derives. The case analyzes a warehouse company’s general situation that operates with apparent effectiveness in the Peruvian market. First, it relates the author’s personal experience who, together with his partner, proposes the generational change in the company between his son and himself, with expectations of an improvement in the management of the company in the face of the imminent and rapid technological innovation. Likewise, the company's problems are exposed because of the death of one of the partners, the constant innovation in the market, and the changes in the chain of command. Faced with this situation, the discussion may focus on the approach to future decisions in the company.